Small oscillations of a viscous incompressible fluid with a large number of small interacting particles in the case of their surface distribution - Berezhnoi, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We study the asymptotic behavior of solutions of the problem that describes small motions of a viscous incompressible fluid filling a domain Ω with a large number of suspended small solid interacting particles concentrated in a small neighborhood of a certain smooth surface Γ ⊂ Ω. We prove that, under certain conditions, the limit of these solutions satisfies the original equations in the domain Ω\Γ and some averaged boundary conditions (conjugation conditions) on Γ.